Drug-induced myocardial dysfunction – recommendations for assessment in clinical and pre-clinical studies. Issue 3 (3rd March 2020) - Ebrahimi, Ahmad; Raichlen, Joel S; Pointon, Amy; Gottfridsson, Christer; Munley, Jiefen; Hockings, Paul; Cartwright, James; Buss, Nicholas; Wikström, Johannes; Gan, Li-Ming; Whittaker, Andrew; Khalil, Ali; et al.
ABSTRACT: Introduction : Drug-induced myocardial dysfunction is an important safety concern during drug development. Oncology compounds can cause myocardial dysfunction, leading to decreased left ventricular ejection fraction and heart failure via several mechanisms. Cardiovascular imaging has a major role in the early detection and monitoring of cardiotoxicity. Echocardiography is the method of choice because of its widespread availability, low cost, and absence of radiation exposure. Cardiac magnetic resonance imaging can provide better reliability, reproducibility, and accuracy in the detection of drug-induced myocardial dysfunction. In addition, it enables assessment of myocardial edema, fibrosis, and necrosis. Cardiac serologic biomarkers such as troponins and B-type natriuretic peptides are used in combination with imaging during drug development. This article provides a general overview of each imaging modality and practical guidance for early detection and monitoring of cardiotoxicity. Areas covered : Cardiovascular imaging modalities and cardiac biomarkers for monitoring of cardiac function and early detection of drug-induced myocardial dysfunction in drug development. Expert opinion : Some new drugs especially in the oncology field, can cause myocardial dysfunction. Depending on the strength of pre-clinical or clinical data, CV imaging modalities and cardiac biomarkers play an important role in the early detection and mitigation plans for such drugs during their development.